Pemanfaatan Buah Bakau Rhizophora sp. dan Sonneratia sp. sebagai Bahan Baku Kopi Analog: Utilization of Mangrove Fruit Rhizophora sp. and Sonneratia sp. as Raw Material for Analog Coffee - Cahya Mirawati Putri; Widya Pangestika; Novi Luthfiyana; Nusaibah Nusaibah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2022)
Mangrove are plants that are commonly found on the coast of Indonesia. However, although mangrove are rich in nutrients and antioxidants, they have not been widely used as consumer goods. Product development from mangrove fruits as raw materials is required, including analog coffee made from the mangrove fruit of Rhizophora sp. and Sonneratia sp. The purpose of this study was to determine the proximate levels, antioxidants and consumer preferences through hedonic testing of each mangrove coffee production. Three raw material treatments used in this study were pure commercial ground coffee arabica type (K0) as a control, analog coffee made from the mangrove fruit Rhizophora sp. (K1), and Sonneratia sp. (K2). The results showed that the percent moisture content was in the range of 3.33-7.31% and the ash content was in the range of 2.57-3.16% of the two parameters, both samples (K1 and K2) had meets the standard SNI for coffee. 01-3542-2004. While the fat content is 9.06% - 12.6% and the protein content 7.09-11.59% of the two parameters, the highest value was achieved with the K2 treatment. Based on the antioxidant activity test in % of the inhibitory units, the percentage results were between 61.63-77.15% with the highest value K2 achieved. Based on the hedonic test, the preference for color (neutral-like), aroma (like), taste (like), texture (like). Differences in the raw materials used have a significant effect on the aroma and color, while taste and texture do not affect the preference.